The effect of zeolite activation and time variation of batch method on the adsorption effectiveness of iron metal ions - Suyanta Suyanta; Sunarto Sunarto; Susila Kristianungrum; Lalang Egalitera Pambayun (Jurnal Penelitian Saintek, 2026)
This study aims to evaluate the effectiveness of three types of zeolite, namely fresh zeolite, saturated zeolite, and zeolite activated using 0.5 M sulfuric acid in adsorbing iron metal ions (Fe³⁺) from simulated wastewater solutions. This study also aims to understand the effect of variations in contact time (1 to 5 days) on the adsorption efficiency of Fe³⁺ ions, as well as to prove whether the activation process is able to regenerate the adsorption capacity of saturated zeolites. The method used is a laboratory-scale batch method, where each type of zeolite is immersed in a 10 ppm FeCl₃ solution for 1 to 5 days. Each treatment was carried out on 15 samples, and the Fe³⁺ ion content after the adsorption process was measured using an Atomic Absorption Spectrophotometer (AAS). Zeolite activation was carried out by immersing saturated zeolite in 0.5 M H₂SO₄ for 24 hours, followed by washing to neutral pH and drying at 200°C.  The results showed that the average efficiency of activated zeolite reached 99.15%, which is only 0.4% smaller than the average adsorption efficiency of fresh zeolite which is 99.55%. Saturated zeolite without activation showed a significant decrease in performance with an average efficiency of only 61.852%. Based on the results of the ANOVA test showing a p-value of 0.001 which is smaller than the p-value of 0.005 in the table, there is a difference in adsorption between activated zeolite and fresh zeolite with saturated zeolite. This indicates that acid activation of zeolite can effectively regenerate the adsorption capacity and extend the service life of zeolite in chemical waste treatment.